Death by black hole: and other cosmic quandaries - Tyson, Neil de Grasse (New York norton company, 2014)
With ease and originality, Tyson illuminates topics ranging from the linguistic merits of astrophysics to the limits of our five senses to the search for life in the universe
1
Keywords: Astrobiology; Black holes (Astronomy); Solar system; cosmology